Safety and Side Effects of Using Placenta-Derived Decidual Stromal Cells for Graft-versus-Host Disease and Hemorrhagic Cystitis - Baygan, Arjang; Aronsson-Kurttila, Wictor; Moretti, Gianluca; Tibert, Babylonia; Dahllöf, Göran; Klingspor, Lena; Gustafsson, Britt; Khoein, Bita; Moll, Guido; Hausmann, Charlotta; Svahn, Britt-Marie; Westgren, Magnus; et al. (Frontiers in Immunology, 2017)
Mesenchymal stromal cells (MSCs) are increasingly used in regenerate medicine. Placenta- derived decidual stromal cells (DSCs) are a novel therapy for acute graft-versus-host-disease (GVHD) and hemorrhagic cystitis (HC) after allogeneic hematopoietic stem cell transplantation (HSCT). DSCs are more immunosuppressive than MSCs. We assessed adverse events and safety using DSCs among 44 treated patients and 40 controls. The median dose of infused cells was 1.5 (range 0.9-2.9) x 10 6 DSCs/kg. The patients were given 2 (1-5) doses, with a total of 82 infusions. Monitoring ended 3 months after the last DSC infusion. Three patients had transient reactions during DSC infusion. Laboratory values, hemorrhages and transfusions were similar in the two groups. The frequency of leukemic relapse (2/2, DSC/controls) and invasive fungal infections (6/6) were the same in the two groups. Causes of death were those seen in HSCT patients: infections (5/3), respiratory failure (1/1), circulatory failure (3/1), thromboembolism (1/0), multiorgan failure (0/1) and, GVHD and others (2/7). One-year survival for the DSC patients with GVHD was 67%, which was significantly better than achieved previously at our center. One year survival was 90% in the DSC treated HC group. DSC infusions appear safe. Randomized studies are required to prove efficacy